2017
DOI: 10.1051/bioconf/20170902033
|View full text |Cite
|
Sign up to set email alerts
|

Charakterisierung der Birnenaromatik von Österreichischem Weißburgunder (Pinot blanc) hinsichtlich Typizität und Qualität

Abstract: Abstract. Austria is the third largest Pinot blanc producing country in the world. Pinot blanc is cultivated on 1916,5 ha of vineyards, which corresponds to 4.3% of the Austrian wine-growing area and 12.3% of the world production of Pinot blanc (15,493 ha). Only in Germany (4794 ha; 30.9%) and in Italy (3086 ha; 19.9%) more Pinot blanc is cultivated. The bouquet of dry Austrian Pinot Blanc is usually discreet, with a predominance of pear and apple flavors, these often coming together with a walnut aroma and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Pear and olfactory intensity, together with spicy, sourness and saltness characterized more V2 after nine months in bottle, than V1. Particularly the pear descriptor was indicated as a typical characteristic of Austrian Pinot blanc wines [10,11], but a high value of the pear descriptor is not necessarily associated with the overall quality of Pinot blanc wine [10], as also reported in the present study. The temporal trend was driven mainly by the increase in various higher linear ethyl and higher acetate esters and it was associated accordingly to higher perceived intensity for apple, tropical and dried fruits descriptors, and a higher overall quality judgment.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Pear and olfactory intensity, together with spicy, sourness and saltness characterized more V2 after nine months in bottle, than V1. Particularly the pear descriptor was indicated as a typical characteristic of Austrian Pinot blanc wines [10,11], but a high value of the pear descriptor is not necessarily associated with the overall quality of Pinot blanc wine [10], as also reported in the present study. The temporal trend was driven mainly by the increase in various higher linear ethyl and higher acetate esters and it was associated accordingly to higher perceived intensity for apple, tropical and dried fruits descriptors, and a higher overall quality judgment.…”
Section: Discussionsupporting
confidence: 81%
“…The flavor of South Tyrolean Pinot Blanc wines was described with apple, pear, citrus, and green notes, occasionally quince and exotic fruits [9]. Also, the aroma of Austrian Pinot Blanc wines has been studied in order to characterize its typical sensory traits; the sensory descriptors evaluated were pear, apple, quince, banana, citrus fruit, apricot, and caramel [10]. A further research highlighted the typicity of Pinot Blanc wine from Austria, stressing out the sensory attribute "pear aroma".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinot blanc wines from South Tyrol are described with the flavour descriptors apple, pear, citrus notes, green notes, occasionally quince and exotic fruit, and in exceptional cases with spicy and nutty notes [7]. Furthermore, it was found that there is a positive correlation between wine quality, typicity and the perceived pear aroma of the Austrian Pinot blanc wines [8]. The perceived pear aroma is difficult to describe, as the studies [8][9][10] show.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was found that there is a positive correlation between wine quality, typicity and the perceived pear aroma of the Austrian Pinot blanc wines [8]. The perceived pear aroma is difficult to describe, as the studies [8][9][10] show. With the representation of sensoryanalytical typograms of the pear aroma, a simple model for the description of the pear aroma has been demonstrated and various influencing parameters on the composition of the typograms discussed [8][9][10].…”
Section: Introductionmentioning
confidence: 99%